Significant Impact of Traditional Yogic Practices with and Without OM Chanting on Psychometric Indices and Academic Performance among Adolescent Girls - Sukanya Rajinikanth; Prabhavathy Devi Narayanan Dass; Haripah Lawanis; Latha R.; Farjana Akter Boby (Physical Rehabilitation and Recreational Health Technologies, 2026)
Purpose. Adolescent girls experience heightened psychological stress affecting academic performance. This study examined the differential effects of traditional yogic practices with and without OM chanting on anxiety, self-confidence, study skills, assertiveness, mindfulness, and academic performance. Materials & Methods. A randomised controlled trial was conducted with 180 adolescent girls aged 14-17 years, who were randomly assigned to yoga with OM chanting (n=60), yoga without OM chanting (n=60), or a control group (n=60). The intervention consisted of 60-minute sessions, five days per week for 12 weeks. Primary outcomes included anxiety (Taylor's Manifest Anxiety Scale), self-confidence (Agnihotri Rekha Self-Confidence Questionnaire), study skills (M Kanchana Study Skills Inventory), assertiveness (Rathus Assertiveness Scale), mindfulness (Mindful Attention Awareness Scale), and academic performance (cumulative grade percentage). Analyses used ANOVA and post-hoc tests. Results. The yoga with OM chanting group demonstrated superior outcomes: anxiety decreased by 42.3% (from 28.4±6.2 to 16.4±4.8) versus 31.7% in yoga without OM chanting (from 28.6±6.4 to 19.5±5.2); self-confidence increased by 38.5% versus 26.8%; mindfulness improved by 44.2% versus 32.1%; and academic performance increased by 18.7% versus 12.4%. Effect sizes for the OM chanting group ranged from medium to large (Cohen's d=0.68-1.24). Conclusions. Traditional yogic practices significantly enhance psychological well-being and academic performance in adolescent girls, with OM chanting providing additional therapeutic benefits. These findings support integration of yoga-based interventions in school settings for adolescent mental health promotion.